Determination of the optical constants of zinc sulphide - Muhamad’, M. R.; Abo-Hassan, Khedr M.; Radhakrishna, S. (Malaysian Journal of Science, 1996)
A method to calculate the optical constants in the transparent region of e-beam sputtered zinc suphide thin film having a direct interband energy gap is reported